Unbalanced Translocation Involving Partial Trisomy 9p and Partial Monosomy Yq With Neurodevelopmental Delays. (April 2013) - Lyons, Michael J.; Fuller, Joshua D.; Montoya, Maria del Carmen; DuPont, Barbara R.; Holden, Kenton R.
We present a 4-year-old Honduran boy with mild neurodevelopmental delays, growth delays, dysmorphic features, and small genitalia. Chromosome analysis initially revealed a single X chromosome and a marker chromosome derived from the short arm of chromosome 9 which was consistent with Turner syndrome as only 1 sex chromosome could be identified. However, on further analysis, he was found to have an unbalanced translocation involving the short arm of chromosome 9 and the long arm of the Y chromosome. The translocation resulted in partial trisomy 9p and partial monosomy Yq. The patient's clinical features are felt to be the result of partial trisomy 9p. In addition, partial monosomy Yq is associated with male infertility. Testing of the patient's parents was normal, indicating this was a de novo translocation. Additional evaluations of this child and his parents allowed an accurate assessment of his diagnosis, long-term prognosis, and chance of recurrence.